Final Year Project Guideline - Nawanir, Gusman; Mahmud, Fatimah; Lee, Chia Kuang (UMP Publisher, 2019)
Final year project (FYP) is one of the core program subjects in the Bachelor of Project Management (Hons) and Bachelor of Industrial Technology Management (Hons), which is intended to expose the students on the process of conducting academic research in their respective area of study while building communication, presentation, writing, and time management skills. In order to achieve these objectives, this module is prepared as a guideline for the final year students of Bachelor of Project Management (Hons) and Bachelor of Industrial Technology Management (Hons) in conducting their FYP within two semesters (i.e., Semester six and seven). It guides them to meet the requirement of FYP, starting from the preparation of a research proposal until the final reporting, besides as a logbook to record their project activities and progress. We expect that this module shall be utilized as a guideline to produce high quality of research proposals, final reports, research papers, and posters. All the best!